Imaging Techniques: Essential Tools for the Study of SARS-CoV-2 Infection - Deroubaix, Aurélie; Kramvis, Anna (Frontiers in Cellular and Infection Microbiology, 2022)
The world has seen the emergence of a new virus in 2019, SARS-CoV-2, causing the Covid-19 pandemic and million deaths worldwide. Microscopy can be much more informative than conventional detection methods such as RT-PCR. This review aims to present the up-to-date microscopy observations in patients, the in vitro studies of the viral proteins and their interaction with their host, discuss the microscopy techniques for detection and study of SARS-CoV-2, and summarize the reagents used for SARS-CoV-2 detection. From basic fluorescent microscopy to high resolution techniques and combined technologies, this article shows the power and the potential of microscopy techniques, especially in the field of virology.